Assessment of Drought Tolerance of Varieties and Samples of Spring Soft Wheats Based on the Length of the Root System - Amanov Oybek Anvarovich; Abror Shoymuradov; Bakhramova Nilufar Nazarovna; Abdusalomova Iroda Nurmurod kizi (Global Scientific Publishing, 2022)
This article presents data on the drought resistance of spring varieties and samples of soft wheat based on the study of the length of the root system under conditions of a provacation background. Based on the study, drought-resistant samples with longer root systems were selected and transferred to the next stages of selection.
Keywords: Plant; root; drought resistance; variety